A Hansel and Gretel approach to cooperative vehicle positioning - Stephenson, Scott; Meng, Xiaolin; Moore, Terry; Baxendale, Anthony; Edwards, Tim (North Coast Media LLC, 2014)
There is little doubt in the benefit gained from cooperative modes of road transport, as agents working together generally perform better. In simple terms, this is the holistic idea that the whole is greater than the sum of its parts, commonly known as synergy. On top of this clear advantage, the complex systems theory of emergence suggests that novel strategies will develop from the as-yet-undefined patterns and structures. It is clear, however, that to facilitate this development certain technological advances need to be achieved. In this case, individual road agents need to accurately identify their location, and communicate easily and safely with other agents. This is a shift away from protective and passive systems toward preventative and active transport safety.